Author cocitation analysis quantitative methods for mapping the intellectual structure of an academic discipline - Eom, Sean B. (IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2009)
"This book introduces an alternative approach to conducting author cocitation analysis (ACA) without relying on commercial citation databases such as index ISI citation index. It is based on a custom bibliographic database and cocitation matrix generation systems specifically developed to use the custom database"--Provided by publisher.